The software architecture for designing interactive mobile computing applications. (13th September 2012) - Bagchi, Susmit
In general, the mobile computing applications based on mobile–client/server model require the synchrony and reliability of Remote Procedure Call (RPC) as well as Inter–Process Communication (IPC) mechanisms. In case of interactive mobile applications, the mobile processes executing at mobile clients coordinate with corresponding server processes through IPC. These interactive mobile computing applications require an integrated framework supporting distributed RPC and IPC mechanisms. This paper proposes novel software architecture integrating IPC and RPC mechanisms in mobile–client/server model to support interactive mobile computing applications offering location transparency and scalability. The software architecture is successfully implemented and evaluated in real–life mobile computing environment.